LipoParticles: Lipid-Coated PLA Nanoparticles Enhanced In Vitro mRNA Transfection Compared to Liposomes - Camille Ayad; Pierre Libeau; Céline Lacroix-Gimon; Catherine Ladavière; Bernard Verrier (MDPI AG, 2021)
The approval of two mRNA vaccines as urgent prophylactic treatments against Covid-19 made them a realistic alternative to conventional vaccination methods. However, naked mRNA is rapidly degraded by the body and cannot effectively penetrate cells. Vectors capable of addressing these issues while allowing endosomal escape are therefore needed. To date, the most widely used vectors for this purpose have been lipid-based vectors. Thus, we have designed an innovative vector called LipoParticles (LP) consisting of poly(lactic) acid (PLA) nanoparticles coated with a 15/85 mol/mol DSPC/DOTAP lipid membrane. An in vitro investigation was carried out to examine whether the incorporation of a solid core offered added value compared to liposomes alone. To that end, a formulation strategy that we have named particulate layer-by-layer (pLbL) was used. This method permitted the adsorption of nucleic acids on the surface of LP (mainly by means of electrostatic interactions through the addition of LAH4-L1 peptide), allowing both cellular penetration and endosomal escape. After a thorough characterization of size, size distribution, and surface charge- and a complexation assessment of each vector-their transfection capacity and cytotoxicity (on antigenic presenting cells, namely DC2.4, and epithelial HeLa cells) were compared. LP have been shown to be significantly better transfecting agents than liposomes through pLbL formulation on both HeLa and DC 2.4 cells. These data illustrate the added value of a solid particulate core inside a lipid membrane, which is expected to rigidify the final assemblies and makes them less prone to early loss of mRNA. In addition, this assembly promoted not only efficient delivery of mRNA, but also of plasmid DNA, making it a versatile nucleic acid carrier that could be used for various vaccine applications. Finally, if the addition of the LAH4-L1 peptide systematically leads to toxicity of the pLbL formulation on DC 2.4 cells, the optimization of the nucleic acid/LAH4-L1 peptide mass ratio becomes an interesting strategy-essentially reducing the peptide intake to limit its cytotoxicity while maintaining a relevant transfection efficiency.